1997
DOI: 10.1246/cl.1997.223
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Dependent Quenching of the Lowest Excited Singlet State of 9,10-Dichloroanthracene by Ground-State 2,5-Dimethylhexa-2,4-diene Yielding 9-Chloroanthracene in Acetonitrile or the [4+2] Adduct in n-Heptane

Abstract: In acetonitrile, an exciplex formed between the lowest excited singlet state (1DCA*) of 9,10-dichloroanthracene (DCA) and ground-state 2,5-dimethylhexa-2,4-diene (DMHD) generates the DCA radical anion as an intermediate for dechlorination of DCA yielding 9-chloroanthracene. In n-heptane, however, quenching of 1DCA* by DMHD forms no exciplex and a dibenzobicyclo[2.2.2]octadiene-type compound (the [4+2] adduct) is obtained as the final product.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…(1) (DBA-DMHD)* formed in acetonitrile (ε = 37.5) or acetone (ε = 20.7) decomposes into DBA• -and the DMHD radical cation (DMHD•+), and DBA• -thus generated is an intermediate for DMHD-assisted DBA -> BA debromination; although Saltiel et al [22,23] reported formation of a DCA-DMHD exciplex (by direct excitation of a ground-state DCA-DMHD complex) or a triplex (by a reaction of a DCA-DMHD exciplex with DMHD), no such evidences were obtained by our previous study [19]. (2) [24], the existence of NR• is reasonable but its decomposition into the original compounds (DBA and DMHD) may be a major process owing to the extremely slow photochemical reaction of DBA (cf.…”
Section: Resultsmentioning
confidence: 64%
See 1 more Smart Citation
“…(1) (DBA-DMHD)* formed in acetonitrile (ε = 37.5) or acetone (ε = 20.7) decomposes into DBA• -and the DMHD radical cation (DMHD•+), and DBA• -thus generated is an intermediate for DMHD-assisted DBA -> BA debromination; although Saltiel et al [22,23] reported formation of a DCA-DMHD exciplex (by direct excitation of a ground-state DCA-DMHD complex) or a triplex (by a reaction of a DCA-DMHD exciplex with DMHD), no such evidences were obtained by our previous study [19]. (2) [24], the existence of NR• is reasonable but its decomposition into the original compounds (DBA and DMHD) may be a major process owing to the extremely slow photochemical reaction of DBA (cf.…”
Section: Resultsmentioning
confidence: 64%
“…5-1 and kE = 1.1 x 10 9 s-1 ) estimated for an exciplex (formed between DCA* and DMHD) on an assumption of diffusion-controlled quenching (kq = 1.9 x 1010 Μ-1 s -1 ) of DCA* by DMHD [19] as well as those (k' = 2.7 x 109 s -1 and kE = 4.8 x 10 9 s -1 ) of an exciplex formed between DBA* and DMA [13]. kq (stated previously) and kE = 3.8x 10 9 s-1 obtained for (DBA-DMHD)* in ethanol are also comparable with those obtained in acetonitrile, but k' = 9.4 x 10 9 s -1 obtained in the former solvent is about 6.7-times greater than that obtained in the latter solvent.…”
Section: Resultsmentioning
confidence: 99%